2012
DOI: 10.1016/j.marpolbul.2011.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale distribution and dynamics of bivalve larvae in a deep atoll lagoon (Ahe, French Polynesia)

Abstract: Bivalve larvae and hydrographic parameters were sampled over a range of spatio-temporal scales in a deep atoll lagoon. Bivalve larvae abundances were very high throughout the year: 18,550 m(-3) in average. Larvae were (i) concentrated at mid-depth with nocturnal ascent and diurnal descent, (ii) heterogeneously dispersed at the lagoon scale, (iii) subject to day-to-day variation in abundance and (iv) transferred between different parts of the lagoon providing evidence of intra-lagoonal connectivity. The primacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
1
29
1
Order By: Relevance
“…15% and 4%, respectively in New Caledonian lagoon; Carassou et al, 2010). In Ahe lagoon, linked to pearl farming, P. margaritifera could constitute a large part of this important bivalve larvae stock, but Thomas et al (2012a) estimated that the contribution of P. margaritifera to this stock would be low (0.5-5%) compared to wild species and in particular to P. maculata (65-91%). This suggests that high bivalve larvae concentration in the lagoon is not drastically modified by pearl oyster farming, despite 10% of the lagoon area dedicated to this activity.…”
Section: Zooplankton Community: Dominance Of Meroplankton and Bivalvementioning
confidence: 99%
See 1 more Smart Citation
“…15% and 4%, respectively in New Caledonian lagoon; Carassou et al, 2010). In Ahe lagoon, linked to pearl farming, P. margaritifera could constitute a large part of this important bivalve larvae stock, but Thomas et al (2012a) estimated that the contribution of P. margaritifera to this stock would be low (0.5-5%) compared to wild species and in particular to P. maculata (65-91%). This suggests that high bivalve larvae concentration in the lagoon is not drastically modified by pearl oyster farming, despite 10% of the lagoon area dedicated to this activity.…”
Section: Zooplankton Community: Dominance Of Meroplankton and Bivalvementioning
confidence: 99%
“…Even with likely more than a few percent of farmed oysters, the relative abundance of bivalve larvae in the Ahe plankton is probably due to the importance of wild populations. The requirement to know the exact status of the wild population of bivalve has been pointed out by several of the study achieved in Ahe (Thomas et al, 2012a). This will be a priority in subsequent studies.…”
Section: Zooplankton Community: Dominance Of Meroplankton and Bivalvementioning
confidence: 99%
“…In situ observations showed that bivalve larvae follow a dial migration toward the surface during the night and toward the bottom during the day (Thomas et al, 2012). The sub-model of vertical migration coupled to the transport model empirically simulated the vertical migration of the larvae depending on the swimming behaviour observed in situ.…”
Section: The Bio-physical Larval Transport Modelmentioning
confidence: 99%
“…Better knowledge of factors controlling recruitment variability will also enable to better understand the wild populations structure and to rationalise a collecting strategy for aquaculture. In particular, gametogenesis, spawning and larval growth potential also determine spat collection variability (Fournier et al, 2012;Thomas et al, 2012). Coupling biology and physic-based approaches is now needed to perpetuate the pearl oyster aquaculture.…”
Section: Consequences For Spat Collectionmentioning
confidence: 99%
See 1 more Smart Citation